Comparative analysis of income taxation of citizens in different countries - Podkorytova A. A., Tavdidishvili A. E. (Research dialogue: Finances and Credit)
the Main objective of this work is a comparative analysis of income taxation of the Russian Federation and the French Republic with the aim of identifying similarities and differences, and advantages and disadvantages of both systems.
Keywords: налогообложение; налоги; Россия; taxes; Russia; Франция; taxation; France